Último día cada día: Y otro escrito sobre cine y filosofía - Martin, Adrian (punctum books, 2013)
Where is the film analysis today? What are you doing, in the dark, the theory of cinema? This field, as it has been professionally defined (at least in the Anglo-American academic world), is currently divided between historians interested in the social context that examine the great formations of modernity, and experts in the style that They demand the return of outmoded things such as authorial vision, tone, and staging. But there are also other currents, vital and inventive, of which we are hardly hearing anything in any of the official channels. Last day each day , which for this edition has been extended with the essay "Avatars of the meeting", shines a light on one of these new and exciting ways.